Emerging Patterns of Antibiotic Susceptibility of Bacterial Pathogens at IAHS Hospital (IAHS Medical Journal, 2026)
Background: Antibiotic resistance is an increasing public health issue in Bangladesh, attributed to the prevalent neglect and overutilization of antibiotics. Inadequate regulatory enforcement and readily available over-the-counter access have contributed to resistance in prevalent bacterial infections. This development presents significant obstacles to efficient treatment and infection management nationwide. To find out the sensitivity and resistance pattern of different antibiotics used for common bacterial infections this research was performed.Materials and methods: This Cross-sectional Descriptive study was done during the period from July 2024 to March 2025 on 60 patients with the evidence of infection includes (20 dissimilar blood samples, urine samples and sputum samples).Results: In Blood samples Salmonella and Staphylococcus aureus show high sensitivity to Meropenem and cephalosporins, while Klebsiella exhibits moderate resistance to fluoroquinolones and cephalosporins. E. coli shows high sensitivity to Meropenem and Nitrofurantoin, while Klebsiella exhibits high resistance to key antibiotics but responds better to Amikacin and Meropenem in urine samples. Klebsiella shows high resistance to cephalosporins, while carbapenems and Amikacin remain effective, Pseudomonas exhibit notable resistance, especially to ceftazidime and piperacillin-tazobactam in sputum.Conclusion: To sum up, the incensing trend of antimicrobial resistance need better monitoring, management and innovation, but depicting how resistance patterns are changing is critical for making therapeutic decisionsIAHS Medical Journal Vol 8(1), June 2025; 17-21